Composite material with GO simultaneously loaded with Ni-TiO2 as well as preparation method and application of composite material
By using easy hydrolyzable Ni-MOF and Ti-MOF materials and composited with graphene, Ni-TiO2-GO composite materials are formed, which solves the thermal stability and kinetic performance of magnesium hydride MgH2 and achieves efficient hydrogen storage and discharge performance promote.
Patent Information
- Application Number
- CN202411368727.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
Among the existing solid hydrogen storage materials, magnesium hydride MgH2 has high thermal stability and slow kinetic properties. The commonly used catalyst nanoTiO2 is prone to agglomeration during hydrogen release, resulting in insufficient maximum hydrogen release.
Using Ni-MOF and Ti-MOF materials with easy hydrolysis properties, metal particles are uniformly dispersed by hydrolysis, and placed in an aqueous graphene solution for recombination, and then converted into Ni-TiO2 with a nano-scale spherical structure by calcination method. GO composite materials use the role of GO's support, template and protective layer to improve catalytic performance.
The initial hydrogen release temperature was reduced and the amount of hydrogen released was increased, with the hydrogen release reaching 7.009-6.768 wt%, and the structural stability and reaction activity of the catalyst were significantly improved, avoiding agglomeration.
Smart Images

Figure CN119263207A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a method for simultaneously loading Ni-TiO 2 Composite materials and preparation methods and applications thereof. Background Art
[0002] At present, magnesium hydride MgH 2 It has a high hydrogen storage capacity of 7.6wt%, and the raw material Mg has high reserves and low cost. 2 There are problems of high thermal stability and slow kinetic performance.
[0003] A common solution is to use transition metals or transition metal oxides as catalysts to increase the hydrogen release kinetics during the reaction by interacting with hydrogen atoms. For example, the existing literature 1 (hao Y, Gao H, Tang Q, et al. Ultra-fine TiO 2 nanoparticles supported on three-dimensionally ordered macroporous structure for improving the hydrogen storage performance of MgH 2 [J]. Applied Surface Science: A Journal Devoted to the Properties of Interfaces in Relation to the Synthesis and Behaviour of Materials, 2022 (May 30): 585.) Based on the controllable preparation of metal oxides, nano-TiO 2 catalyst and doped it into MgH 2 In. Make MgH 2 The initial dehydrogenation temperature dropped from 60°C to 219.5°C. The direct reason for the above technical effect is that the TiO 2 The particles are nanoparticles with a size of 10-15 nm. However, the problem with this technical solution is that the maximum hydrogen release capacity is only 5.95 wt%. The reason for the above problem is that the nano TiO prepared by this technical solution 2 Agglomeration occurs during the subsequent catalytic dehydrogenation process, resulting in inability to fully catalyze dehydrogenation.
[0004] The most common solution to solve the agglomeration problem during hydrogen release is to introduce a carrier to improve the dispersion of metal particles. For example, the existing literature 2 (Liu G, Wang L, Hu Y, et al. Enhanced Catalytic Effect of TiO 2 @rGO Synthesized by One-pot Ethylene Glycol-assisted Solvothermal Methodfor MgH 2 [J]. Journal of Alloys and Compounds, 2021, 881: 160644. DOI: 10.1016 / j.jallcom.2021.160644.) Reduced graphene oxide-loaded titanium dioxide nanoparticles were hydrothermally synthesized by simultaneously using reduced graphene oxide dispersion and tetrabutyl titanate by a solvothermal method, achieving a final hydrogen release of 6.7wt%; and, through comparative experiments, it was proved that the introduction of reduced graphene oxide increased the hydrogen release from 6.3wt% to 6.7wt%. However, the problem with this technical solution is that the initial hydrogen release temperature of the hydrogen storage material is too high, at 240°C. The reason for the above problem is that the simultaneous addition of nano-titanium dioxide and reduced graphene oxide causes the nano-titanium dioxide to stack, resulting in H 2 The reduction of the desorption energy barrier is not obvious. From the perspective of its role in the technical solution, it can be concluded that the reduced graphene oxide only plays the role of a template in the technical solution.
[0005] The inventor of the present invention has found, based on existing literature and previous research by the research group, that graphene materials play three main roles in the technical solution: carrier, template or protective layer. The specific role can be determined by the specific operation of adding graphene. For example, in the existing document 3 (Sun Lixian, Yu Yuqian, Xu Fen, et al. A graphene shell-coated Co-MOF-74 composite material and its preparation method and application: CN202210357424.8 [P]. CN202210357424.8 [2024-09-24].), graphene and metal particles for synthesizing MOF are added to the reactor at the same time for solvothermal synthesis. The result is that the original MOF particle size is 0.2-0.3 μm, and the particle size of the composite material after synthesis is increased to 2-3 μm, that is, after adding graphene and metal particles for synthesizing MOF at the same time, the size of the composite material will increase, so that the contact area of the composite material reaction process is greatly reduced; at the same time, the morphology and shape of the MOF synthesized by this method are basically unchanged, and the catalytic rate cannot be increased by improving the morphology to increase the reaction active sites. In other words, in this technical solution, the role of graphene is the role of the template agent, and, in order to achieve the above purpose, graphene and metal source ions are added simultaneously. It is the above operations that directly lead to the increase in the size of MOF materials.
[0006] In addition, in another preliminary study of the inventors of the present invention, MOF materials were introduced to improve catalytic performance by utilizing the characteristics of controllable structure and high crystallinity of MOF materials. For example, in the existing document 4 (Chu Hailiang, Wei Qiuhong, Xia Yongpeng, et al. A nitrogen-doped porous carbon-coated ruthenium-embedded cobalt phosphide composite material based on graphene oxide [P]. Guangxi Zhuang Autonomous Region: CN202210502981.4, 2022-08-09.), RuCo-MOF was selected, which has the inherent stability of Ru precious metal. The improved MOF material has higher stability than the original MOF material and can still maintain a higher crystallinity in aqueous solution, that is, it overcomes the problem that the original Co-MOF is easily hydrolyzed in water, and in order to further improve the stability of the Co-MOF material, graphene materials are introduced as protective layers and carriers. Although this technical solution effectively improves the stability of the composite material and achieves the purpose of the invention, this technical solution inevitably has the problem that when graphene and MOF materials are added at the same time, the contact area with graphene is limited due to the high crystallinity of Co-MOF, which ultimately reduces the loading amount of nanoparticles. Summary of the invention
[0007] The purpose of the present invention is to provide a GO simultaneously loaded with Ni-TiO 2 Composite materials and preparation methods and applications thereof.
[0008] In view of the technical problems existing in the prior art, the basic technical principle of the present invention is to select Ni-MOF and Ti-MOF materials with easy hydrolysis properties at the same time, and use the characteristics of hydrolysis to achieve uniform dispersion of metal particles, and at the same time, make Ni and Ti composite; in order to maintain the dispersibility of the metal particles formed by hydrolysis, MOF is placed in a graphene aqueous solution for hydrolysis, even if the metal particles produced by hydrolysis are directly loaded on the graphene surface; finally, Ni and Ti are converted into nanoscale spherical structures by calcination. In addition, since the selected MOF material has the characteristics of hydrolysis, the preparation conditions of the MOF material must be in an organic solvent.
[0009] The specific functions of each component in the present invention are:
[0010] 1. Ni and Ti elements are catalytic in themselves, and the two metal elements can also form a synergistic effect, that is, provide a hydrogen pump function;
[0011] 2. The role of GO in the technical solution is different from that in the conventional technical solution. In the conventional technical solution, GO serves as a single carrier, template or protective layer, while in the technical solution of the present invention, GO has the above three roles at the same time.
[0012] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0013] A kind of GO simultaneously loaded with Ni-TiO 2 The composite material is prepared by using tetrabutyl titanate, dimethylformamide, nickel nitrate hexahydrate, terephthalic acid, and a single-layer graphene aqueous solution as raw materials, and Ni-MOF / Ti-MIL-125 is obtained by a solvothermal method. Then, Ni and Ti are compounded with GO by utilizing the hydrolysis characteristics of MOF materials to obtain Ni-Ti-GO. Finally, Ni-TiO 2 -GO;
[0014] The Ni-TiO 2 The microstructure of -GO is Ni-TiO supported on a single layer of graphene oxide. 2 , where the substrate is GO and the surface is loaded Ni-TiO 2 Microspheres, size 0.1-0.15 μm.
[0015] A kind of GO simultaneously loaded with Ni-TiO 2 The method for preparing a composite material comprises the following steps:
[0016] Step 1, preparation of Ni-MOF / Ti-MIL-125, first, dimethylformamide is added to methanol to obtain solution A, and at the same time, terephthalic acid and tetrabutyl titanate are dissolved in solution A to obtain solution B, then nickel nitrate hexahydrate is added to solution B to obtain a mixed solution C, and the mixed solution C is subjected to a hydrothermal reaction under certain conditions. After the reaction is completed, the mixed solution C is subjected to centrifugal washing at a centrifugal washing speed of 5000-6000 rpm and a centrifugal washing time of 3-5 minutes. Finally, the centrifugal product is vacuum dried at a drying temperature of 60-80°C and a drying time of 12-24 hours to obtain Ni-MOF / Ti-MIL-125;
[0017] In the step 1, the molar ratio of dimethylformamide, terephthalic acid, tetrabutyl titanate and nickel nitrate hexahydrate is 10:1:1:5;
[0018] In step 1, the hydrothermal reaction conditions are: the hydrothermal time is 20-24h, and the hydrothermal temperature is 150-160°C;
[0019] Step 2, preparation of Ni-Ti-GO, first, the Ni-MOF / Ti-MIL-125 obtained in step 1 and the monolayer graphene oxide GO satisfy a certain mass ratio, the Ni-MOF / Ti-MIL-125 is placed in a GO aqueous solution, and stirred for 1 hour to obtain a solution D, then centrifuged at a speed of 5000-6000 rpm for 3-5 minutes, and finally, the centrifuged product is vacuum dried at a drying temperature of 60-80°C for 12-24 hours to obtain Ni-Ti-GO;
[0020] In step 2, the mass ratio of Ni-MOF / Ti-MIL-125 to GO is 10:1, and the molar concentration of the GO aqueous solution is 0.1 mg / mL;
[0021] Step 3, Ni-TiO 2 Preparation of Ni-Ti-GO: calcining the Ni-Ti-GO obtained in step 2 under certain conditions can obtain GO and load Ni-TiO 2 The composite material is referred to as Ni-TiO 2 -GO;
[0022] In step 3, the calcination conditions are: the calcination temperature is 500° C. and the calcination time is 2 h.
[0023] A Ni-TiO-based 2 Preparation method of magnesium hydride composite hydrogen storage material based on MgH 2 and Ni-TiO2 -GO meets a certain mass ratio and is ball-milled under certain conditions to obtain Ni-TiO-based 2 -GO magnesium hydride composite hydrogen storage material, referred to as Mg / Ni-TiO 2 -GO;
[0024] The MgH 2 and Ni-TiO 2 -GO mass ratio is 93:7;
[0025] The ball milling conditions are as follows: the ball milling speed is 400-450 rpm, the ball milling time is 8-10 h, and the ball-to-material ratio is 40:1.
[0026] A Ni-TiO-based 2 -GO magnesium hydride composite hydrogen storage material, Mg / Ni-TiO 2 -When GO is used as a hydrogen storage material, the initial dehydrogenation temperature is 182-205°C. When the dehydrogenation temperature is 250°C, the hydrogen release amount is 3.66-3.82wt%; under the conditions of a hydrogen absorption temperature of 30°C and a hydrogen absorption time of 3550-3600s, the hydrogen absorption amount is 1.80-1.81wt%.
[0027] The technical effects of the present invention have been tested and the specific contents are as follows:
[0028] The present invention is tested by EDS and XRD and it is known that Ni-TiO 2 -GO contains both Ni and TiO 2 The characteristic peaks of Ni and Ti are also present, indicating that Ni-TiO 2 -GO was successfully synthesized;
[0029] Combining the SEM test results and XRD test results of the present invention, it can be seen that the sheet structure is a single layer of graphene oxide, and the nanospheres are Ni metal particles and TiO 2 Particles, Ni-TiO 2 The size is 0.1-0.15μm;
[0030] The dehydrogenation performance test of the present invention shows that Ni-TiO 2 When the doping amount of Ni-TiO is 5-9wt%, the starting dehydrogenation temperature ranges from 205-182℃ and the dehydrogenation amount ranges from 7.009-6.768wt%. 2 -When the GO doping content is 7wt%, the hydrogen release amount is 3.66-3.82wt%.
[0031] Compared with the prior art, the present invention has the following advantages:
[0032] 1. Using MOF materials with hydrolysis characteristics to obtain an amorphous structure through hydrolysis, thereby effectively improving the dispersibility of metal particles;
[0033] 2. Use GO to increase the loaded Ni-TiO 2 The structure is stable to avoid agglomeration;
[0034] 3. The raw materials used are commercially available, the process is simple, and low energy consumption and pollution are achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 XRD patterns of Ni-MOF / Ti-MIL-125 and Ti-MIL-125 prepared in Example 1
[0036] Figure 2 The Ni-TiO prepared in Example 1 2 XRD patterns of -GO and Ni-Ti-GO
[0037] Figure 3 is the SEM image of the Ti-MIL-125 prepared in Example 1;
[0038] Figure 4 is the SEM image of the Ni-MOF / Ti-MIL-125 prepared in Example 1;
[0039] Figure 5 is the SEM image of the Ni-Ti-GO prepared in Example 1;
[0040] Figure 6 The Ni-TiO prepared in Example 1 2 -SEM image of GO;
[0041] Figure 7 The Ni-TiO prepared in Example 1 2 -EDS pattern of GO;
[0042] Figure 8 The Mg / Ni-TiO prepared in Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 2 -GO-7, Mg / Ni-TiO 2 -GO-9, Mg / Ni-TiO 2 -GO-5, MgH 2 TPD diagram;
[0043] Fig. 9 For pure ball-milled MgH 2 PCT diagrams at 300°C, 325°C, and 350°C;
[0044] Fig.10The prepared Mg / Ni-TiO 2 - PCT diagram of GO-7 at 275℃, 300℃, and 325℃;
[0045] Fig.11 The prepared Mg / Ni-TiO 2 -GO-7 at 125℃, 100℃, 75℃, 50℃, 30℃ and MgH 2 PCT plot at 150°C. DETAILED DESCRIPTION
[0046] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0047] Example 1
[0048] A kind of GO simultaneously loaded with Ni-TiO 2 The method for preparing a composite material comprises the following steps:
[0049] Step 1, preparation of Ni-MOF / Ti-MIL-125, first, add 27mL of dimethylformamide to 3mL of methanol to obtain solution A, then, dissolve 1.5g of terephthalic acid and 1mL of tetrabutyl titanate in solution A to obtain solution B, then, add 1g of nickel nitrate hexahydrate to solution B to obtain a mixed solution C, then, at a reaction temperature of 150°C and a reaction time of 24h, subject the mixed solution C to a hydrothermal reaction, after the reaction is completed, centrifuge washing is performed at a centrifugal washing speed of 6000rpm and a centrifugal washing time of 3min, finally, the centrifugal product is vacuum dried at a drying temperature of 60°C and a drying time of 12h to obtain Ni-MOF / Ti-MIL-125;
[0050] In order to prove the composition of Ni-MOF / Ti-MIL-125, XRD test was carried out. The test results are shown in Figure 1 As shown, Ni-MOF / Ti-MIL-125 has characteristic peaks of both Ni-MOF and Ti-MIL-125. The test results show that step 1 successfully prepared Ni-MOF and Ti-MIL-125 at the same time and compounded the two materials.
[0051] In order to verify the microstructure of Ni-MOF / Ti-MIL-125, SEM test was performed. Meanwhile, for comparison, Ti-MIL-125 was prepared and SEM test was performed.
[0052] The SEM test results of Ti-MIL-125 are as follows Figure 3As shown, the microstructure of Ti-MIL-125 is a regular polyhedron structure with chamfers, and the size is 1-2μm;
[0053] The SEM test results of Ni-MOF / Ti-MIL-125 are shown in Figure 4 As shown, the basic microstructure of Ni-MOF / Ti-MIL-125 is also a regular polyhedron structure with chamfers, with a size of 1-2 μm, and nanorods are also loaded on the surface of the regular polyhedron structure.
[0054] Combining the SEM test results with the XRD test results, it can be seen that the nanorods are Ni-MOF, that is, Ni-MOF is loaded on the Ti-MIL-125 surface in the form of nanorod structure.
[0055] Step 2, preparation of Ni-Ti-GO, first, the mass ratio of Ni-MOF / Ti-MIL-125 obtained in step 1 to monolayer graphene oxide GO is 2:1, Ni-MOF / Ti-MIL-125 is placed in a GO aqueous solution, and stirred for 1 hour to obtain solution D, then centrifuged at a centrifugal washing speed of 6000 rpm and a centrifugal washing time of 3 minutes, and finally, the centrifuged product is vacuum dried at a drying temperature of 60°C and a drying time of 12 hours to obtain Ni-Ti-GO;
[0056] In order to prove the composition of Ni-Ti-GO, XRD test was carried out. The test results are shown in Figure 2 As shown in the figure, the Ni-Ti-GO obtained in step 2 has no obvious diffraction peaks, that is, the characteristic peaks of Ni-MOF and Ti-MIL-125 disappear. The reason is that since step 2 is carried out under aqueous solution conditions, and Ni-MOF and Ti-MIL-125 have the characteristics of easy hydrolysis, the product obtained in step 2 decomposes into an amorphous state in water, so there is no obvious characteristic peak.
[0057] In order to verify the microstructure of Ni-Ti-GO, SEM test was performed. The test results are shown in Figure 5 As shown, the test results show that the microscopic morphology of Ni-Ti-GO is the presence of nanoparticles on the flakes, and the size of the nanoparticles is 0.2-0.3μm.
[0058] Combining the SEM test results with the XRD test results, it can be seen that the lamellar structure is a single layer of graphene oxide, and the nanoparticles are Ni metal particles and Ti metal particles after the hydrolysis of Ni-MOF / Ti-MIL-125.
[0059] Step 3, Ni-TiO 2Preparation of Ni-Ti-GO: calcining the Ni-Ti-GO obtained in step 2 at a calcination temperature of 500 °C and a calcination time of 2 h to obtain GO loaded with Ni-TiO 2 The composite material is referred to as Ni-TiO 2 -GO;
[0060] In order to prove that Ni-TiO 2 -GO composition, EDS test and XRD test were carried out.
[0061] EDS test results are as follows Figure 7 As shown, Ni-TiO 2 -GO contains Ni and Ti elements at the same time, and the elements are evenly distributed in Ni-TiO 2 -GO surface;
[0062] XRD test results are as follows Figure 2 As shown, Ni-TiO 2 -GO contains both Ni and TiO 2 Compared with step 2, the calcination process in step 3 decomposes the organic framework in MOFs, converts the metal elements and replaces them with Ni and TiO 2 The form exists in composite materials.
[0063] In order to prove that Ni-TiO 2 -GO microstructure, SEM test. The test results are as follows Figure 6 As shown, Ni-TiO 2 The microscopic morphology of -GO is that there are nano-microspheres on the layer structure, and the size of the nano-microspheres is 0.1-0.15μm.
[0064] Combining the SEM test results with the XRD test results, it can be seen that the sheet structure is a single layer of graphene oxide, and the nanospheres are Ni metal particles and TiO 2 particle.
[0065] In order to prove that Ni-TiO 2 -GO as MgH 2 Effect of hydrogen storage catalysts prepared based on Ni-TiO 2 -GO magnesium hydride composite hydrogen storage material, the specific method is to use MgH 2 and Ni-TiO 2 The mass ratio of MgH-GO was 93:7. Under the conditions of ball milling speed of 400 rpm, ball milling time of 8 h and ball-to-material ratio of 40:1, MgH 2 and Ni-TiO 2 -GO mixed ball milling can obtain Ni-TiO 2-GO magnesium hydride composite hydrogen storage material, specifically in step 3 of embodiment 1, the material is based on Ni-TiO 2 -GO magnesium hydride composite hydrogen storage material is named Mg / Ni-TiO 2 -GO-7; at the same time, for comparison, pure MgH 2 Pure ball-milled MgH 2 .
[0066] In order to prove that Mg / Ni-TiO 2 -GO-7 was subjected to TPD test for hydrogen release performance. At the same time, pure ball-milled MgH 2 Perform TPD test.
[0067] Pure ball-milled MgH 2 The TPD test results are as follows Figure 8 As shown, the initial hydrogen release temperature is 280°C;
[0068] Mg / Ni-TiO 2 -GO-7 TPD test results are as follows Figure 8 As shown in the figure, the initial dehydrogenation temperature is 183 °C, which is higher than that of pure ball-milled MgH 2 The initial hydrogen release temperature was reduced by 97°C;
[0069] At 250℃, Mg / Ni-TiO 2 -GO-7 has a hydrogen release amount of 3.66-3.82 wt%.
[0070] The test results show that Ni-TiO 2 -GO has very good catalytic performance. The reason is that during the dehydrogenation process, Ni and Ti atoms can form Mg 2 Ni、Mg 2 NeA 4 , the hydrogen pump formed by the Ti-H bond and the MgH 2 reaction, thereby reducing the strength of the Mg-H bond and accelerating the H + transmission, ultimately significantly reducing the dehydrogenation temperature.
[0071] To further prove that Mg / Ni-TiO 2 -GO-7 was subjected to PCT test for hydrogen release performance. At the same time, for comparison, pure ball-milled MgH 2 Get a PCT test.
[0072] Pure ball-milled MgH 2 The hydrogen release performance test results are as follows Fig. 9 As shown, at 325 °C, the time to reach the maximum amount of hydrogen release is 1200 s;
[0073] Mg / Ni-TiO 2 -GO-7 hydrogen release performance test results are as follows Fig.10 As shown, at 325 °C, the time to reach the maximum amount of hydrogen release is 300 s;
[0074] The test results show that under the same dehydrogenation conditions, adding Ni-TiO 2 -GO as a catalyst can significantly improve the hydrogen desorption kinetics by nearly 6 times.
[0075] Pure ball-milled MgH 2 The low temperature hydrogen absorption test results are as follows Fig.11 As shown, the hydrogen absorption time is 30 min, the hydrogen absorption amount reaches 0.80 wt%, and the required hydrogen absorption temperature is 150 °C;
[0076] Mg / Ni-TiO 2 -GO-7 low temperature hydrogen absorption test results are as follows Fig.11 As shown, the hydrogen absorption time is 30 min, the hydrogen absorption amount reaches 0.82 wt%, and the required hydrogen absorption temperature is only 30 °C;
[0077] The test results show that when the test conditions are the same time and the same hydrogen absorption, Mg / Ni-TiO 2 -GO-7 is better than pure ball-milled MgH 2 The hydrogen absorption temperature of Mg / Ni-TiO is 120℃ lower. 2 -GO-7 still has excellent hydrogen absorption performance at room temperature 30℃.
[0078] In order to prove the role of GO in the technical solution, comparative example 1 is provided, a Ni-TiO 2 Composite materials and Ni-TiO based 2 Magnesium hydride composite hydrogen storage material.
[0079] Comparative Example 1
[0080] A Ni-TiO 2 The steps not specifically described are the same as those in Example 1, except that step 2 is not performed, and the Ni-MOF / Ti-MIL-125 obtained in step 1 is directly subjected to step 3 to obtain Ni-TiO 2 Composite material, referred to as Ni-TiO 2 ; And, the subsequent preparation based on Ni-TiO 2 Magnesium hydride composite hydrogen storage material, referred to as Mg / Ni-TiO 2 -7.
[0081] Ni-TiO 2 The XRD test results are as follows Figure 2As shown, Ni-TiO 2 Contains both Ni and TiO 2 The characteristic peaks of Example 1 are basically the same.
[0082] Mg / Ni-TiO 2 -7 TPD test results are as follows Figure 8 As shown, the initial hydrogen desorption temperature is 183°C, which is also substantially the same as that in Example 1.
[0083] By combining the XRD test results with the TPD test results, it can be seen that GO has no substantial effect on the initial hydrogen desorption temperature.
[0084] At 250℃, Mg / Ni-TiO 2 -7 has a hydrogen release capacity of 2.5-2.6wt%. Compared with Example 1, adding GO can significantly increase the hydrogen release capacity by 46.6%-46.9%. The reason is that during the reaction, Mg can transition to the π antibonding orbital of GO, thereby increasing the H 2 dissociation, effectively increasing MgH 2 The catalytic rate of hydrogen release process increases with the increase of MgH 2 The amount of hydrogen released per unit time.
[0085] In order to prove that Ni-TiO 2 -The effect of the amount of GO added on the hydrogen storage performance, providing comparative examples 2 and 3, Ni-TiO 2 -GO addition amounts are 5wt.% and 9wt.% of magnesium hydride composite hydrogen storage materials respectively.
[0086] Comparative Example 2
[0087] A Ni-TiO 2 The preparation method of the magnesium hydride composite hydrogen storage material with a 5wt.% addition amount of GO, the steps not specifically described are the same as those in Example 1, except that: when the magnesium hydride composite hydrogen storage material is used, MgH 2 and Ni-TiO obtained in step 3 2 The mass ratio of Mg / Ni-TiO 2 -GO named Mg / Ni-TiO 2 -GO-5.
[0088] MgH 2 / Ni-TiO 2 -The TPD test results of GO-5 are as follows Figure 8 As shown, the initial hydrogen release temperature is 205°C; the maximum hydrogen release amount is 7.009wt%
[0089] By comparing with Example 1, it can be seen that Ni-TiO2 When the amount of GO added is too small, although it can also reduce the initial hydrogen desorption temperature, it cannot form enough Mg 2 NeA 4 The electron channel is blocked, resulting in a decrease in the concentration of the formed hydrogen pump. At the same time, the reaction active sites are reduced, which ultimately leads to a lack of obvious improvement in the catalytic effect.
[0090] Comparative Example 3
[0091] A Ni-TiO 2 The preparation method of the magnesium hydride composite hydrogen storage material with a 9wt.% addition amount of GO, the steps not specifically described are the same as those in Example 1, except that: when the magnesium hydride composite hydrogen storage material is used, MgH 2 and Ni-TiO obtained in step 3 2 The mass ratio of Mg / Ni-TiO 2 -GO named Mg / Ni-TiO 2 -GO-9.
[0092] MgH 2 / Ni-TiO 2 -GO-9 TPD test results are as follows Figure 8 As shown, the initial hydrogen desorption temperature is 182°C; the maximum hydrogen desorption amount is 6.770wt%.
[0093] By comparing with Example 1, it can be seen that Ni-TiO 2 When the amount of Ni-TiO-GO added is too much, although the effect of reducing the initial hydrogen desorption temperature is further improved, the maximum theoretical hydrogen production decreases due to the excessive amount of catalyst added, which leads to a significant decrease in the maximum hydrogen desorption amount. 2 -The amount of GO added should not be too much.
Claims
1. A composite material of GO and Ni-TiO2, characterized in that: Tetrabutyl titanate, dimethylformamide, nickel nitrate hexahydrate, terephthalic acid, and a single-layer graphene aqueous solution were used as raw materials to obtain Ni-MOF / Ti-MIL-125 through a solvothermal method. Ni and Ti were then compounded with GO by utilizing the hydrolysis characteristics of the MOF material to obtain Ni-Ti-GO. Finally, Ni-TiO2-GO was obtained through a calcination method.
2. The composite material of GO and Ni-TiO2 simultaneously loaded according to claim 1, characterized in that: The microscopic morphology of the Ni-TiO2-GO is Ni-TiO2 supported on a single layer of graphene oxide, wherein the substrate is GO and the surface layer is supported Ni-TiO2 microspheres with a size of 0.1-0.15 μm.
3. A method for preparing a composite material of GO and Ni-TiO2, characterized in that The following steps are involved: Step 1, preparation of Ni-MOF / Ti-MIL-125, first, dimethylformamide is added to methanol to obtain solution A, and at the same time, terephthalic acid and tetrabutyl titanate are dissolved in solution A to obtain solution B, then nickel nitrate hexahydrate is added to solution B to obtain a mixed solution C, and the mixed solution C is subjected to a hydrothermal reaction under certain conditions. After the reaction is completed, the mixed solution C is subjected to centrifugal washing at a centrifugal washing speed of 5000-6000 rpm and a centrifugal washing time of 3-5 minutes. Finally, the centrifugal product is vacuum dried at a drying temperature of 60-80°C and a drying time of 12-24 hours to obtain Ni-MOF / Ti-MIL-125; Step 2, preparation of Ni-Ti-GO, first, the Ni-MOF / Ti-MIL-125 obtained in step 1 and the monolayer graphene oxide GO satisfy a certain mass ratio, the Ni-MOF / Ti-MIL-125 is placed in a GO aqueous solution, and stirred for 1 hour to obtain a solution D, then centrifuged at a speed of 5000-6000 rpm for 3-5 minutes, and finally, the centrifuged product is vacuum dried at a drying temperature of 60-80°C for 12-24 hours to obtain Ni-Ti-GO; Step 3, preparation of Ni-TiO2-GO, calcining the Ni-Ti-GO obtained in step 2 under certain conditions to obtain a composite material in which GO and Ni-TiO2 are simultaneously loaded, referred to as Ni-TiO2-GO.
4. The preparation method according to claim 1, characterized in that: In the step 1, the molar ratio of dimethylformamide, terephthalic acid, tetrabutyl titanate and nickel nitrate hexahydrate is 10:1:1:5; In step 1, the hydrothermal reaction conditions are: the hydrothermal time is 20-24h, and the hydrothermal temperature is 150-160°C.
5. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of Ni-MOF / Ti-MIL-125 to GO is 10:1, and the molar concentration of the GO aqueous solution is 0.1 mg / mL; In step 3, the calcination conditions are: the calcination temperature is 500° C. and the calcination time is 2 h.
6. A method for preparing a magnesium hydride composite hydrogen storage material based on Ni-TiO2-GO, characterized in that: By meeting a certain mass ratio of MgH2 and Ni-TiO2-GO and performing ball milling under certain conditions, a magnesium hydride composite hydrogen storage material based on Ni-TiO2-GO can be obtained, which is referred to as Mg / Ni-TiO2-GO for short.
7. The method for preparing the magnesium hydride composite hydrogen storage material according to claim 6, characterized in that: The mass ratio of MgH2 to Ni-TiO2-GO is 93:
7.
8. The method for preparing the magnesium hydride composite hydrogen storage material according to claim 6, characterized in that: The ball milling conditions are as follows: the ball milling speed is 400-450 rpm, the ball milling time is 8-10 h, and the ball-to-material ratio is 40:
1.
9. A magnesium hydride composite hydrogen storage material based on Ni-TiO2-GO, characterized in that: When Mg / Ni-TiO2-GO is used as a hydrogen storage material, the initial dehydrogenation temperature is 182-205°C, and when the dehydrogenation temperature is 250°C, the amount of hydrogen released is 3.66-3.82wt%.
10. A magnesium hydride composite hydrogen storage material based on Ni-TiO2-GO, characterized in that: When Mg / Ni-TiO2-GO is used as a hydrogen storage material, the hydrogen absorption amount is 1.80-1.81wt% under the conditions of hydrogen absorption temperature of 30°C and hydrogen absorption time of 3550-3600s.
Citation Information
Patent Citations
Co-MOF-74 composite material coated with graphene shell as well as preparation method and application of Co-MOF-74 composite material
CN114682302A
Cited By
Modified magnesium hydride composite material as well as preparation method and application thereof
CN120681720A
Hollow spherical titanium-nickel oxide heterojunction and preparation method and application thereof
CN122538130A